Marketing strategy of the Church in Russian Federation - Myasnikova, Valeriya (2017)
This bachelor thesis introduces in the beginning the basic theory of marketing.The second part presents theoretical framework of the Church.The final part consists of defining if the Russian Orthodox Church can be called a business company, the possibility of use marketing strategies by religious organizations, creating marketing mix for the church and the survey.